REMODELING OF THE RAT GASTRIC WALL COMPONENTS UNDER THE EFFECT OF COMPLEX FOOD ADDITIVES - Yachmin, A.I.; Bilash, V.P.; Yeroshenko, G.A.; Білаш, С.М.; Shevchenko, K.V.; Ryabushko, О.B.; Vatsenko, А.V.; Solod, А.В. (World of Medicine and Biology, 2020)
The purpose of the study was to establish the dynamics of changes in the metric components of the structural components of the rat gastric wall with long-term use of a complex of food additives: sodium nitrite, sodium glutamate and Ponceau 4R. The use of a complex of food additives (monosodium glutamate, sodium nitrite and Ponceau 4R leads to structural and metric changes in the fundus of the fundus of the stomach. At 4 weeks is determined by severe hyperhydration and microcirculation disorders in all membranes. Other components do not recover to the values in the control group, destructive phenomena develop in the mucous membrane, and pronounced leukocyte infiltration in the submucosal.
Keywords: gastric wall; sodium nitrite; sodium glutamate; Ponceau 4R; rats